Exploring generation Z's use of AI advice in business decision-making - Correia, Inês Monteiro Saraiva (2024)
There is an increasing number of companies employing AI in business decision-making. Companies are composed by a diverse workforce with different experiences and backgrounds thus, it becomes imperative to understand if generations rely differently on AI. This thesis aims to understand the differences between Generation Z and Generation X regarding their reliance on AI advice and explore how this relationship is affected by trust. Additionally, it assesses the moderating effect of confidence in own judgement. To collect the data, a quantitative betweensubjects survey was employed, where participants from both generations were presented with two hypothetical decision-making scenarios to evaluate their reliance on AI advice. Findings reveal that Gen Z relies more on AI advice compared to Gen X. Interestingly, no significant differences were found in dispositional trust in AI between the two generations. However, a strong positive correlation was identified between dispositional and situational trust, with situational trust significantly enhancing reliance on AI advice. This indicates that higher levels of situational trust are correlated with greater reliance on AI. Surprisingly, the moderating effect of confidence in own judgment was not confirmed. Exploratory analysis suggests that familiarity with AI might mediate the relationship between generational differences and reliance on AI advice. Additionally, it was found that higher confidence in own judgement negatively impacts reliance on AI advice. These insights underscore the complexity of understanding how trust affects reliance on AI across generational cohorts and highlight the importance of considering this factor in order to foster effective AI integration strategies within companies.